Corporate investments in startups: CVC unit vs. direct investment - Kwon, Sungjoung; Manna, Nomalia (Journal of Banking & Finance, 2025)
A significant fraction of corporate investments in startups are made directly without relying on corporate venture capital (CVC) units. Moreover, most firms making investments via CVC programs also make direct investments. We show that such direct investments are utilized to flexibly respond to investment opportunities over a short period of time: (1) firms respond to a competition shock by sharply increasing direct investments; (2) firms rely on direct investments when startups are easier to evaluate in the short term; and (3) direct investments are less likely to be followed up. We find no evidence that direct investments are used to entrench managers.